A RasGAP SH3 peptide aptamer inhibits RasGAP-Aurora interaction and induces caspase-independent tumor cell death. - Perayot Pamonsinlapatham (PLoS ONE, 2008)
The Ras GTPase-activating protein RasGAP catalyzes the conversion of active GTP-bound Ras into inactive GDP-bound Ras. However, RasGAP also acts as a positive effector of Ras and exerts an anti-apoptotic activity that is independent of its GAP function and that involves its SH3 (Src homology) domain. We used a combinatorial peptide aptamer approach to select a collection of RasGAP SH3 specific ligands. We mapped the peptide aptamer binding sites by performing yeast two-hybrid mating assays against a panel of RasGAP SH3 mutants. We examined the biological activity of a peptide aptamer targeting a pocket delineated by residues D295/7, L313 and W317. This aptamer shows a caspase-independent cytotoxic activity on tumor cell lines. It disrupts the interaction between RasGAP and Aurora B kinase. This work identifies the above-mentioned pocket as an interesting therapeutic target to pursue and points its cognate peptide aptamer as a promising guide to discover RasGAP small-molecule drug candidates.